Stress signaling in breast cancer cells induces matrix components that promote chemoresistant metastasis - Insua-Rodríguez, Jacob; Lowy, Camille; Sinn, Peter; Spaich, Saskia; Sütterlin, Marc; Schneeweiss, Andreas; Oskarsson, Thordur (EMBO molecular medicine, 2018)
Metastatic progression remains a major burden for cancer patients and is associated with eventual resistance to prevailing therapies such as chemotherapy. Here, we reveal how chemotherapy induces an extracellular matrix (ECM), wound healing, and stem cell network in cancer cells via the c‐Jun N‐terminal kinase (JNK) pathway, leading to reduced therapeutic efficacy.